Implementasi Undang-Undang Nomor 18 Tahun 2008 Tentang Kebijakan Dan Strategi Pengelolaan Sampah Dalam Meningkatkan Pelayanan Publik : Studi Pada Dinas Pekerjaan Umum, Perhubungan, Komunikasi Dan Informatika Kabupaten Pangandaran (Jurnal Manajemen Kreatif dan Inovasi, 2025)
Based on the author's initial observations, it is known that the Public Works, Transportation, Communication and Informatics Agency of Pangandaran Regency in implementing the waste/cleanliness service policy is not optimal. The research method used in this study is a descriptive research method with a qualitative approach. The primary data in this study is data obtained from interviews with informants directly. While secondary data sources are data collected from other sources which can be in the form of documents related to the problem being studied, The Public Works, Transportation, Communication and Informatics Agency in Pangandaran District, Pangandaran Regency has not been able to implement policies on waste management properly. This can be seen in the implementation of waste management which is not in accordance with the waste management mechanism according to Law of the Republic of Indonesia Number 18 of 2008 concerning Waste Management. The obstacles faced in the implementation of waste management policies by the Public Works, Transportation, Communication and Informatics Agency of Pangandaran Regency are as follows: The technology for waste management is not yet available, Waste sorting has not been carried out by separating organic and non-organic waste, and The place and machine for recycling waste are not yet available. Efforts made to overcome obstacles in the Implementation of Waste Management Policies by the Public Works, Transportation, Communication and Informatics Agency in Pangandaran District, Pangandaran Regency, namely: Submitting an application to the local government so that waste shredding and recycling machines are budgeted in the upcoming APBD, Cooperating with third parties (private sector) in terms of waste management and sorting, and Designing a place to recycle waste.